2016
DOI: 10.2147/ijn.s111447
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of ZnO nanoparticles on mouse testicular cells

et al.

Abstract: Nanoscience and nanotechnology are developing rapidly, and the applications of nanoparticles (NPs) have been found in several fields. At present, NPs are widely used in traditional consumer and industrial products, however, the properties and safety of NPs are still unclear and there are concerns about their potential environmental and health effects. The aim of the present study was to investigate the potential toxicity of ZnO NPs on testicular cells using both in vitro and in vivo systems in a mouse experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
72
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 74 publications
7
72
0
Order By: Relevance
“…From this XRD pattern analysis, we determined the peak intensity, position and width, and full width at half maximum data. The diffraction peaks located at 32.84°, 34.52°, 36.33°, 46.63°, 57.71°, 63.96°, 68.13°, and 69.18° have been keenly indexed as hexagonal wurtzite phase of ZnO, 29,30 and it also confirms further that the synthesized nanopowder was free of impurities as it did not contain any characteristic XRD peaks other than ZnO peaks. According to the diffraction pattern, the synthesized ZnO NP diameter was 20 nm using Debye-Scherrer formula.…”
Section: Results and Discussion Characterization Of Zno Npssupporting
confidence: 55%
See 2 more Smart Citations
“…From this XRD pattern analysis, we determined the peak intensity, position and width, and full width at half maximum data. The diffraction peaks located at 32.84°, 34.52°, 36.33°, 46.63°, 57.71°, 63.96°, 68.13°, and 69.18° have been keenly indexed as hexagonal wurtzite phase of ZnO, 29,30 and it also confirms further that the synthesized nanopowder was free of impurities as it did not contain any characteristic XRD peaks other than ZnO peaks. According to the diffraction pattern, the synthesized ZnO NP diameter was 20 nm using Debye-Scherrer formula.…”
Section: Results and Discussion Characterization Of Zno Npssupporting
confidence: 55%
“…It is also evident that significant sharp absorption of ZnO indicates the monodispersed nature of the NP distribution. 26,29 The absorption spectroscopy data revealed that both the chemically and biologically prepared ZnO NPs showed similar spectral images. Figure 1B represents the XRD pattern of ZnO nanopowder.…”
Section: Results and Discussion Characterization Of Zno Npsmentioning
confidence: 98%
See 1 more Smart Citation
“…106 Generally, silver, GO, zinc oxide, and PdNPs are known to induce ROS generation and eventually cause cell death. 36,48,61,62 TSA induced apoptosis in breast cancer cells through mitochondrial respiratory chains and increased ROS generation. 63 Therefore, the combination of both rGO-Ag and TSA causes enhanced production of ROS and is responsible for cell death.…”
mentioning
confidence: 99%
“…In previous studies, it was reported that the cytotoxic and genotoxic activities increased in various cells such as MCF-7 (Elavarasan et al, 2017) and MDA-MB-231 human breast cancer cells (Roshini et al, 2017) treated with ZnO alone. In a research carried out on mouse testicular cells, it was pronounced that ZnO NPs induced apoptosis through DNA damage caused by reactive oxygen species (Han et al, 2016). There are ZnO NPs induced genotoxicity studies in the literature.…”
Section: Discussionmentioning
confidence: 99%